A facile template-free electrodeposition method for vertically standing nanorods on conductive substrates and their applications for photoelectrochemical catalysis. (23rd March 2017) - Wang, Jue; Gupta, Arunava; Pan, Shanlin
Abstract: A facile template-free electrodeposition technique is developed for large-scale fabrication of vertically standing silver nanorods (NRs) on transparent and conductive substrates. The diameter, length, and surface coverage of Ag NRs are dependent on the electrodeposition time and choice of substrates. The growth mechanism of vertically standing Ag NRs is investigated by tracking their morphology evolution as a function of deposition time. Because of their large specific surface area, oriented alignment, broad range light scattering, and light absorption tunability, these vertically standing NRs can be used as ideal substrates for thin layer photocatalysts for enhancing light absorption and charge collection. Preliminary tests on photoelectrochemical performance of bare Ag NRs, CdS modified Ag NRs, and Ag NRs converted to Ag2 S NRs are presented. This simple NR fabrication method has been successfully applied to prepare Fe NRs as well. This technique can be extended to other conductive substrates and other materials for obtaining vertically standing NR structures. Graphical abstract: Highlights: A facile template-free electrodeposition technique is developed for large-scale fabrication of Ag nanorods. The diameter, length, and surface coverage of Ag NRs are dependent on the electrodeposition time and choice of substrates. This technique can be extended to other materials for obtaining vertically aligned NR structures. Vertically standing NRs in large scale have the potential to increase photocatalysis efficiency.